Catestanin - a promising biological marker for heart failure: A review - Amina M. Alieva; Natalia V. Teplova; Elena V. Reznik; Olga A. Ettinger; Rashad A. Faradzhov; Elvira A. Khachirova; Irina V. Kovtiukh; Irina A. Kotikova; Diana A. Sysoeva; Il'dar R. Bigushev; Igor G. Nikitin (ZAO "Consilium Medicum", 2022)
The epidemic of heart failure (HF) is one of the problems that the global health system has been facing for decades. HF is a multicomponent clinical syndrome caused by dysfunction of the heart and its pathological remodeling. In addition to the well-known natriuretic peptides, a number of cardiovascular biological markers have now been identified that provide clinicians with additional opportunities in diagnosing, classifying, predicting, and monitoring the effectiveness of treating patients with HF. From the position of establishing the sympathetic load in patients with HF, it seems very promising to assess the concentrations of catestatin. The presented data of our literature review suggest that catestatin is probably a reliable biological marker of the activity of the sympathetic division of the autonomic nervous system, and its elevated concentrations in patients with HF reflect the severity of the pathological process. However, despite the reliable results of studies, the clinical significance of assessing the values of this marker both separately and in the framework of a multimarker model requires further study in larger prospective clinical studies.